S56 Moving lentiviral-based gene therapy into a first-in-man CF trial. (12th November 2015) - Griesenbach, U; Alton, EWFW; Beekman, JM; Boyd, AC; Chan, M; Davies, JC; Davies, LA; Davidson, HE; Dekkers, JF; Gea-Sorli, S; Gill, DR; Hasegawa, M; et al.
Abstract : The UK CF Gene Therapy Consortium has developed a pipeline of vectors to deliver CFTR into the airway epithelium. The first of these (plasmid/liposome complexes) recently completed a Phase IIb trial. Anticipating that increased efficiency of gene transfer will be required, we have developed an F/HN-pseudotyped lentivirus which is ~2 logs more efficient in lung gene transfer than non-viral vectors, a single administration lasts for the lifetime of a mouse, and can be repeatedly administered. This vector is targeted for a first-in-man study in 2016, and in preparation for this we have assessed (1) selection of the most efficient promoter/enhancer for lung gene transfer, (2) assessment of toxicity "benchmarked" against the leading non-viral formulation including mapping of integration sites, (3) determination of transduction efficiency which will be used to inform dose-ranging in the trial and characterisation of the cell types transduced by the vector, (4) understanding the impact of pre-existing and acquired anti-viral immunity on transduction efficiency and toxicity, (5) confirmation of CFTR expression and function in relevant models and (6) comparison of vector stability in a jet and single-pass mesh nebuliser. Data will be presented for each of these components, which we believe support progression into human studies. Trial design as well as a regulatory-compliant toxicology study will also be discussed.